PERMASALAHAN CORPORATE SOCIAL RESPONSIBILITY (CSR) DALAM RANGKA PEMBERDAYAAN MASYARAKAT - Retnaningsih, Hartini (Jurnal Aspirasi, 2015)
The background of this paper is the ineffectiveness of implementation of Corporate Social Responsibility (CSR) in many companies. This paper analysis about problems in CSR implementation. The methodology of this paper is literature study. CSR that is regulated in Law No. 40 Year 2007 on Limited Liability Companies and Law No. 25 of 2007 on Investment, is company commitment to build a better quality of life together with the parties (inside or outside the company) to contribute to a sustainable economy. In this case the empowerment of the community is a part of the commitment. The result of analysis showed that the concept of CSR is good, but unfortunately that until now so many companies do not implement CSR properly. Therefore, it is necessary to evaluate the implementation of programs related to CSR, so the program can be implemented on an ongoing basis and can empower communities.